PHARMACOECONOMIC ANALYSIS OF THE THERAPY OF СHRONIC OBSTRUCTIVE PULMONARY DISEASE PATIENTS IN HOSPITAL CONDITIONS - E. E. Vidyakina; S. V. Malchikova (IRBIS LLC, 2016)
Objective. To determine the priority used to vital drugs in сhronic obstructive pulmonary disease (COPD) patients in hospitals of the Kirov region.Materials and Methods. We analyzed 143 medical records of the patient, the analysis of cost of illness, ABC\ VEN - analysis.Results. The results of АВС analysis show that the percentage correlation of medicines of different groups generally corresponds to the recommended norm. The results of VEN analysis prove that the number of vital drugs is decreased while the number of second line drugs is increased.Conclusion. Most of the financial costs were for the treatment of exacerbations of COPD, the appropriate Federal clinical guidelines, simultaneously, there is an active assignment of the second line drugs. Reducing their use and rational therapy of acute conditions will enable competently reallocate financial resources in favour of vital drugs to increase the effectiveness of treatment and reduce the cost of inpatient care.